Evaluation and improvements of ground deformation within the zone of influence of vacuum PVD technique - Nissanka, Honnantarage Don Madeesh Priyamal; Chao, Geoff; Pham, Huy Giao; Salisa Chaiyaput (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Vacuum preloading with prefabricated vertical drains (PVDs) to improve the soft ground has been one of the most popular ground improvement methods in Indonesia. However, the surface cracks caused during vacuum preloading extent up to a considerable distance with a risk of damaging the surrounding areas. Although the principles of vacuum preloading are well presented in the literature, there has been a limited number of studies focused on the deformations of the nearby non-treated area. In this study, evaluation of the zone of influence was done through finite element modeling. Based on the calibrated numerical model, Zone of influence was identified, and minimum stress change required to cause the surface cracks were calculated and presented in this paper. Furthermore, to improve and avoid the zone of influence the design techniques were introduced, and new design technique of gradually reducing the PVD length towards the edge showed a significant reduction of zone of influence, and use of a half-spaced PVD zone to control the deformation has also prevented the occurrence of excessive deformations and results indicate that half-spacing technique combined with reduced length PVD can increase the rate of settlement as well The effect of silty clay layer on zone of influence was also investigated, and it is concluded that the presence of high-permeable silty clay layers at the top surface results in higher vacuum lockage which was a major factor for causing the zone of influence. Stress deformation analysis represent that the zone of influence can be minimized by installing sand-cement columns or sheet piles at the edge of the treated area, and use of vacuum preloading combined with conventional surcharge preloading considerably reduces the total stresses and the zone of influence outside the treated area.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Geotechnical and Earth Resources Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Vertical drains; Soil stabilization